Evaluation of synthetic dye decolorization capacity in Ischnoderma resinosum - Eichlerová, I; Homolka, L; Nerud, F (Journal of industrial microbiology & biotechnology, 2006)
The little studied white rot fungus Ischnoderma resinosum was tested for its ability to decolorize seven different synthetic dyes. The strain efficiently decolorized Orange G, Amaranth, Remazol Brilliant Blue R, Cu-phthalocyanin and Poly R-478 on agar plates and in liquid culture at a relatively high concentration of 2-4 and 0.5-1 g l(-1), respectively. Malachite Green and Crystal Violet were decolorized to a lower extent up to the concentration of 0.1 g l(-1). Decolorization capacity of I. resinosum was higher than that in Phanerochaete chrysosporium, Pleurotus ostreatus or Trametes versicolor. In contrast with these thoroughly examined fungi, I. resinosum was able to degrade a wide spectrum of chemically and structurally different synthetic dyes. I. resinosum also efficiently decolorized dye mixtures. In liquid culture, Orange G and Remazol Brilliant Blue R were decolorized most rapidly; the process was not affected by different nitrogen content in the media. Shaken cultivation strongly inhibited the decolorization of Orange G.
Keywords: Basidiomycota; Coloring Agents; chemické látky znečišťující vodu; odpad tekutý - odstraňování; Waste Disposal, Fluid; Water Pollutants, Chemical; Biodegradation, Environmental; Color; barvicí látky; biodegradace; barva